The Future of Anglican Studies - Joslyn-Siemiatkoski, Daniel (Journal of Anglican studies, 2022)
The papers in this forum offer an interdisciplinary assessment of the state of the field of Anglican Studies and perspectives on future trajectories. The first three papers, on liturgy, history, and world Anglicanism, offer an assessment of the respective state of these areas of Anglican Studies. The second set, on theology, sociology of religion, and biblical studies, stake out positions on how these disciplines inform the work of Anglican Studies. A concluding essay offers a synthesis of these papers, focusing on the themes of local contexts for Anglicanism, a further complexification of decolonizing processes in Anglicanism, and the critical role of conversation in Anglican Studies regarding disciplines, languages, and power dynamics.